2009
DOI: 10.1002/pits.20460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness and efficiency of oral and written retellings and passage review as strategies for comprehending text

Abstract: The purpose of this study was to compare the instructional effectiveness and efficiency of oral retelling, written retelling, and passage review comprehension strategies on third-grade students' accuracy and rate of answering reading comprehension questions. A modified alternating treatment design was used to compare the effects of oral retelling, written retelling, and passage review strategies. Each strategy occurred within the context of repeated readings with phrase drill error correction. This study exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
6
0
2
Order By: Relevance
“…The result of hypothesis 1 was in line with the success of the studies conducted by Moss (1997), Schisler (2008), Lin (2010), and Manywari (2013) that the written retelling technique could strengthen students' reading comprehension. Inevitably, the failure of the previous research described in the earlier section, e.g., Johnson (2008), and Natalie (2009) were rejected because the evidence of hypothesis 1 did not show the insignificance of the written retelling technique on students' reading comprehension.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The result of hypothesis 1 was in line with the success of the studies conducted by Moss (1997), Schisler (2008), Lin (2010), and Manywari (2013) that the written retelling technique could strengthen students' reading comprehension. Inevitably, the failure of the previous research described in the earlier section, e.g., Johnson (2008), and Natalie (2009) were rejected because the evidence of hypothesis 1 did not show the insignificance of the written retelling technique on students' reading comprehension.…”
Section: Discussionsupporting
confidence: 80%
“…Despite the use of written retelling technique in teaching reading for first and second language, the previous studies elaborated earlier disclose a gap. The contradiction between the significance and insignificance of the written retelling technique results has emerge The research evidences reveal that written retelling technique can give impact on students' reading comprehension (Moss, et al 1997;Schisler, 2008;Lin, 2010;Manywari, 2013), but other studies employing the written retelling technique find that the technique could not support teaching of reading comprehension (Johnson, 2008;Natalie, 2009). Studies need to be conducted to verify the insignificance of written retelling technique as some studies have indicated, and to fulfill the absence of research on the topic in EFL research context in Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Students must use their language skills as reading, writing, listening, speaking, summarizing, and interpreting, among others (Lapp et al, 2010). Students must read or listen to a story by using appropriate strategies for reading or listening (Schisler et al, 2010). Then, students must recall, interpret, organize, and summarize the story, extracting the main ideas and key terms (John et al, 2003).…”
Section: Retellingmentioning
confidence: 99%
“…Skinner, Belfiore et al () demonstrated how precisely measuring learning rates allowed researchers to establish that the rapid rates of presentation (1 second) would result in more rapid increases in Bob's word reading. Other educators and researchers have conducted similar studies and shown that strategies and procedures that appear to enhance learning rates (when researchers evaluate them using crude measures of instructional time) actually retard learning (Cates et al, ; Joseph & Nist, ; Nist & Joseph, ; Schisler, Joseph, Konrad, & Alber‐Morgan, ; Skinner et al, ). Others have compared intervention effectiveness more precisely by holding instructional time constant across competing remedial procedures (e.g., Carroll, Skinner, Turner, McCallum, & Masters, ; Grafman & Cates, ; Poncy, Skinner, & Jaspers, ; Skinner et al, ).…”
Section: Measuring Learning Ratesmentioning
confidence: 99%